2018
DOI: 10.1002/star.201800159
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of an In Vitro Low‐Digestible Rice Starch by Addition of Grass Carp Protein Hydrolysates and Its Possible Mechanisms

Abstract: Starch‐containing foods with a high glycemic index and deficiency protein cannot meet the consumers’ proactive demand. Thus, the objective of this work is to test the effect of the presence of grass carp protein hydrolysates (GCPHs) on the digestive and structural properties of pristine rice starch (PRS) during the treatment of high pressure homogenization in combination with spray‐drying (HPH‐SP), and its possible mechanisms. The results show that, when the mass ratio of PRS: GCPHs increases from 100:0 to 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…Atomic force microscopy (AFM) can be used to reveal nanoscale structural features of samples, which are considerably smaller than those observable by CLSM (Niu et al, 2017;Xiao, Niu, Wu, Li, & He, 2019;Xiao & Zhong, 2017). AFM studies have demonstrated that the number and height of protrusions on the surfaces of starch-protein hydrolysate mixtures were significantly altered, compared to those of starch-only samples, suggesting that protein hydrolysates can affect the aggregation of amylose and amylopectin on a nanoscale (Kong et al, 2016;Niu et al, 2017;Xiao et al, 2019;Xiao & Zhong, 2017).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
See 2 more Smart Citations
“…Atomic force microscopy (AFM) can be used to reveal nanoscale structural features of samples, which are considerably smaller than those observable by CLSM (Niu et al, 2017;Xiao, Niu, Wu, Li, & He, 2019;Xiao & Zhong, 2017). AFM studies have demonstrated that the number and height of protrusions on the surfaces of starch-protein hydrolysate mixtures were significantly altered, compared to those of starch-only samples, suggesting that protein hydrolysates can affect the aggregation of amylose and amylopectin on a nanoscale (Kong et al, 2016;Niu et al, 2017;Xiao et al, 2019;Xiao & Zhong, 2017).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…starch granule-channel proteins and starch granule-surface proteins) might be involved in the formation of crystalline structures or that the operative extraction methods partially destroyed starch crystallites J o u r n a l P r e -p r o o f 29 (Hu et al, 2017;Zhan et al, 2020). Moreover, processing operations can influence the multi-scale structures of starch-protein systems, possibly by promoting interactions between starches and proteins which lead to specific structures (Chen, Luo, et al, 2019;Chi, Li, Zhang, Chen, & Li, 2018;Li et al, 2018;Qiu et al, 2015;Xiao et al, 2019). For instance, starches (corn and potato) complexed with soybean peptide, subjected to HMT, have been reported to display higher relative crystallinity than their non-HMT counterparts, which was attributed to interactions between starch chains and side-chain groups in the soybean peptide during HMT (Chen, Luo, et al, 2019).…”
Section: Long-range Molecular Ordered Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The ATR-FTIR spectra of starches were measured using a Nicolet iS50 FTIR spectroscopy (Thermo Scientific, Waltham, MA, USA) with a built-in diamond attenuated total reflection (ATR). The spectral region of 1200-800 cm −1 was deconvoluted with a half-band width and enhancement factor of 19 cm −1 and 1.9, respectively (Xiao et al, 2019).…”
Section: Attenuated Total Reflectance-fourier Transform Infrared Spectroscopy (Atr-ftir) Analysismentioning
confidence: 99%
“…Previous studies have shown that higher soluble protein had greater influence on the gelatinization properties of starch [ 16 ]. It is also indicated that small molecular weight proteins had a stronger effect on the inhibition of starch retrogradation or digestibility than large molecular weight proteins [ 17 , 18 ]. Therefore, it is feasible to regulate the physico-chemical properties of starch-based food products by changing the properties of protein.…”
Section: Introductionmentioning
confidence: 99%